Ultrasonic assisted extraction of thymol from Plectranthus amboinicus (Lour.) spreng leaves - Zahari, Nur Amirah Asifa Raisha (2019)
Plectranthus amboinicus is a medicinal herb with aromatic smells. They are commonly used in food processing and eaten as vegetables. P.amboinicus is also used to relief burn and control asthma. Scientific research on the leaves of this plant reveals that it possesses many beneficial bioactivities and its extract from leaves has a great potential to be used in developing commercial products. However, there is a lack of research on the processing aspects to process its bioactive extract. This research studied two main processes including drying of the leaves using tray dryer and solid-liquid extraction using ultrasonic assisted extraction (UAE). Drying kinetics and mathematical modelling on P. amboinicus leaves were studied. The durations for the drying process are 18, 46 and 74h for 55, 45 and 35 °C, respectively. Midilli and Kucuk model was found to be the most fitted model on the drying kinetic modelling with R2 of 0.998, 0.999 and 0.979 for temperatures of 55, 45 and 35 °C, respectively. The effective moisture diffusivity, Deff was calculated with values of 7.63 x 10-9 m2/s (55 °C), 2.29 x 10-9 m2/s (45 °C) and 1.14 x 10-9 m2/s (35 °C). The activation energy is at 77.78 kJ/mol. The DPPH scavenging values are 80.63, 71.70, and 60 % for each sample dried at temperatures of 35, 45 and 55 °C, respectively. Ultrasonic assisted extraction (UAE) was used as the extraction method to extract thymol concentration. The extraction kinetics and modelling were done at 3 different temperatures. The extracted thymol concentration is the lowest at 60 °C as compared to 40 and 25 °C. The Equilibrium-dependent solid-liquid extraction (EDSLE) model was chosen as the best-fitted model for the kinetic modelling. The R2 values are 0.99, 0.95 and 0.93 for temperatures of 25, 40 and 60 °C, respectively. The optimum parameters for thymol extraction from P.amboinicus are at temperature of 55°C, 23 min of extraction and ratio of solute to solvent (g/mL) at 1: 35. The mechanism of UAE was explained based on observation of the structure changes using Scanning Electron Microscope (SEM). The finding of this study suggested that, increasing of drying temperature will shorten the drying time using the tray drier. UAE is a suitable method to extract thymol from P. amboinicus leaves.